2021
DOI: 10.1142/s0218001421590278
|View full text |Cite
|
Sign up to set email alerts
|

An Improved Artificial Neural Network Model for Flights Delay Prediction

Abstract: With the limitation of air traffic and the rapid increase in the number of flights, flight delay is becoming more frequent. Flight delay leads to financial and time losses for passengers and increases operating costs for airlines. Therefore, the establishment of an accurate prediction model for flight delay becomes vital to build an efficient airline transportation system. The air transportation system has a huge amount of data and complex operation modes, which is suitable for analysis by using machine learni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…Tanik et al [21] studied the company's financial crisis prediction model by combining genetic algorithm and moderate financial indicators, and the results showed that the prediction model had high accuracy compared with other prediction models. Nagendran et al [22] studied a set of financial crisis warning models by adopting the method of ensemble learning and compared it with the neural network algorithm. The research results showed that the accuracy of the algorithm model was higher than that of the neural network algorithm.…”
Section: Introductionmentioning
confidence: 99%
“…Tanik et al [21] studied the company's financial crisis prediction model by combining genetic algorithm and moderate financial indicators, and the results showed that the prediction model had high accuracy compared with other prediction models. Nagendran et al [22] studied a set of financial crisis warning models by adopting the method of ensemble learning and compared it with the neural network algorithm. The research results showed that the accuracy of the algorithm model was higher than that of the neural network algorithm.…”
Section: Introductionmentioning
confidence: 99%